Stakeholder perspectives for optimization of tuberculosis contact investigation in a high-burden setting. - Diana Marangu; Hannah Mwaniki; Salome Nduku; Elizabeth Maleche-Obimbo; Walter Jaoko; Joseph Babigumira; Grace John-Stewart; Deepa Rao (PLoS ONE)
Introduction Optimal tuberculosis contact investigation impacts TB prevention, timely case finding and linkage to care, however data on routine implementation in high burden contexts is limited. Materials and methods In a multi-method qualitative study based on individual interviews with TB patients, facility observations and focus group discussions with health workers (HWs) in 13 public health facilities, and key informant interviews with governmental and non-governmental experts, we describe TB contact investigation in the context of an urban setting in Kenya and identify opportunities for optimization. Results Invitation of TB patients to bring close contacts by HWs was key for all patient decisions that led to contact screening in addition to patients' understanding of TB transmission and desire to avoid contacts suffering from TB. Sub-optimal HW enquiry of TB patients and contacts presenting at the facility were missed opportunities which stemmed from lack of standardized operational procedures, documentation tools and HW training. Stakeholders proposed provision of fast tracked and holistic health packages for contacts seeking TB screening, and sustainable government led funding for the requisite infrastructure and workforce. Conclusion TB contact invitation by HWs leading to contact screening occurs in this context. Stakeholder perspectives inform the design of an operational framework for optimized delivery.